The Situation in Latvian Agriculture in the Context of European and Global Agricultural Trends - Svarinska, Zanna (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2012)
This scientific paper presents a consequent research of actual problems, trends and challenges in agricultural sector worldwide, in Europe and Latvia starting from global outlook and ending up with Latvian nationwide scale. The analysis of global and EU agricultural trends and problems has revealed that they all to a greater or lesser extent refer to Latvia as well. Thus, it can be stated that an analysis and application of worldwide experience in solution of Latvian agricultural problems would be utmost precious and useful, while taking into account not only mature economies as Scandinavian countries, but also experience of developing countries to which Latvian agriculture is more related. Novelty of this research consists of a consequent analysis of the situation in Latvian agricultural sector in the context of European and global agricultural trends. Practical effect of this research is based on the conclusion that the Common Agricultural Policy of the EU does not have any sufficient economic feasibility, as the EU Member States are not uniform in their vision of common agricultural policy, but separated in country groups with different agricultural problems and trends.